2022
DOI: 10.1038/s41531-022-00358-z
|View full text |Cite
|
Sign up to set email alerts
|

Lack of full sequencing GBA1 studies for patients with Parkinson’s disease in Latin America

Abstract: Full sequencing of the GBA1 gene in patients with Parkinson’s disease provides a wide screening of pathogenic variants, but less developed regions of the world, like Latin America, may have difficulties in performing full sequencing. We performed a systematic review with meta-analysis to explore the prevalence and the odds ratio of specific GBA1 variants in Parkinson’s disease in Latin America. We noted a lack of full sequencing GBA1 studies in Latin America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
1
0
0
Order By: Relevance
“…This difference in prevalence might arise because only a third of the included studies in our systematic review fully sequenced the gene (Table S3). Similar findings have been highlighted within our region before, 112 who showed that due to gene complexity, many studies within the region performed incomplete sequencing.…”
Section: Discussionsupporting
confidence: 90%
“…This difference in prevalence might arise because only a third of the included studies in our systematic review fully sequenced the gene (Table S3). Similar findings have been highlighted within our region before, 112 who showed that due to gene complexity, many studies within the region performed incomplete sequencing.…”
Section: Discussionsupporting
confidence: 90%